A three to five phase matrix converter for a stand-alone power supply including the PMSM motor drive system - Hanamoto, Tsuyoshi; Amino, M.; Toosi, Saman; Mailah, Nashiren Farzilah; Misron, Norhisam (Faculty of Computer Science and Information Technology, Universiti Putra Malaysia, 2015)
This paper presents a novel electrical power supply system for a stand-alone system using a three to five phase matrix converter (MC). MCs are able to convert AC to AC power directly without DC link capacitors and it is used as the power conversion system, because arbitrary output, AC to AC and AC to DC, is obtained to use adequate switching pattern. Here, one three phase AC output for the power supply of a surface mounted permanent magnet synchronous motors (SPMSMs) speed control, and one DC output for battery storages system are demonstrated as applications of the MC. To realize the system, direct duty ratio pulse width modulation (DDPWM) is supposed to achieve the desired output. Giving the adequate switching pattern for the MC, the mixed AC/DC output systems are able to control independently. The validity of the proposed method is shown using MATLAB/Simulink simulation.